PENDUGAAN POTENSI TEGAKAN DAN KONTRIBUSI HUTAN RAKYAT TERHADAP PENDAPATAN MASYARAKAT DI KECAMATAN CIGUDEG KABUPATEN BOGOR - Bakti, Galih Febriana; Supriono, Bambang; Meiganati, Kustin Bintani (Universitas Nusa Bangsa, 2018)
Forests are one of the great natural resources of its role in various aspects of life both economic aspects, social, development and forest environment and its ecosystem as the basis of national development capital with the diversity of flora and fauna that can provide benefits for human life. One effort to support the balance of natural ecosystems and economic needs is the formation of community forests, aimed at increasing the income and welfare of the people. This can be seen from the existence of traditional folk forests in the effort of the community itself without the intervention of the government (pure self-help), either in the form of one species plant (pure forest), or with the pattern of agroforestry. The purpose of knowing about the potential and condition of community forest, and the amount of revenue contribution from the result of community forest management is compared with Minimum Regional Wage (UMR) Bogor Regency. Methods in this study using survey approach and analyzed qualitatively and quantitatively by using systematic sampling with random start with 20% sampling intensity. The result of research on the potential of community forest stands is 1.213,586 m3, derived from Sengon, Jabon, Acacia, Mahogany and Jati. The contribution of peasant forest income is on average 29,88% compared to UMR value of Bogor Regency.